1173 Airway and Breathing Problems in Pierre Robin Sequence: A Systematic Review Protocol. (12th October 2021) - Ramjeeawon, A; van der Plas, P; van de Lande, L; Ong, J; Wyatt, M; Abel, F; Kangesu, L; Sommerlad, B; Navaratnarajah, J; Wolvius, E; Laverty, A; Bulstrode, N
Abstract: Aim: The primary aim is to systematically review the specific airway and/or breathing problems which have been reported in Pierre Robin Sequence (PRS). Secondary aims are to understand the prevalence and severity of these airway and breathing problems, and options for screening, assessment, and monitoring. Method: A search strategy will be designed to search the following databases: MEDLINE, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials(CENTRAL) including a grey literature search, to identify publications on airway and/or breathing problems in Pierre Robin Sequence patients. Airway or breathing problems to be included are defined upper airway conditions (e.g., sleep apnoea) or clinically or objectively defined airway/breathing problems (e.g., increased respiratory rate, polysomnography). Screening will exclude non-English articles, abstracts, letters, editorials, expert opinions and breathing problems not anatomically related to craniofacial underdevelopment. Results: This systematic review has been successfully registered on the PROSPERO International Prospective Register of Systematic Reviews (CRD42020210572) Conclusions: PRS is a rare craniofacial condition which presents at birth, consisting of micrognathia, glossoptosis and airway problems, and is usually, but not always, associated with a cleft palate. There is no consensus on the type of airway problems that affect patients with PRS. The findings of this systematic review will help to develop a consensus on the airway and breathing problems in PRS and options for assessment and monitoring of the airway and breathing problem. This data may also contribute to development of a standardized guideline for management of airway and breathing problems in PRS.